The Effect of Organizational Culture, Innovation Climate, and Job Satisfaction on Affective Commitment (Case Study of PT. Java Connection) - Diva Alvina; Didik Subiyanto; Tri Ratna Purnamarini (Dinasti International Journal of Education Management And Social Science, 2025)
This research aims to examine the effect of organizational culture on improving employee performance at PT. Java Connection. The population and sample consisted of 40 company employees. Because the number of samples is the same at the population, the census (or saturated) sampling method is used, where all members of the population are part of the sample. This research is categorized as causal associative, which aims to identify the relationship between variables. Data processing and analysis involved descriptive statistics, testing of research instruments (validty, reliability, and classical assumption tests), multiple regression analysis, and hypothesis testing (t-test and F-test), all of which were carried out using SPSS version 26. The results of this study indicate that (1) Organizational Culture has a positive influence on Affective Commitment, (2) Innovational Climate has a positive influence on Affective Commitment, (3) Job Satisfaction has a positive influence on Affective Commitment, (4) Organizational Culture, Innovation Climate, and Job Satisfaction simultaneously influence Affective Commitment.